Bringing Knowledge to Truth: The Joke and Australian (In)Humanities - McConaghy, Cathryn (The Australian Journal of Indigenous Education, 2005)
Abstract In the formulation of new humanities – knowledge, truth and social action brought together in the defence of what makes us human in this place and time – there is also the need to identify the obstacles to honouring our humanity. This paper continues the task of critically examining contemporary forms of inhumanity, in this instance as perpetuated by a liberal Australian government against its citizens and others. Liberalism, by nature, enables the co-existence of contradictory practices that both protect and deny human rights and dignities. In psychoanalytic terms, the defence of liberties and its repressed other, the denial of them, are both present in such states. Because of their links with both the conscious and the unconscious, an analysis of jokes provides insights into these contradictory processes. The paper explores how both the humanities and the inhumanities are manifest variously in the joking behaviours of social groups.